PHYTOCHEMICAL COMPOSITION OF PSYCHOTRIA DAILZELLI LEAVES - ABHISHEK. M,; KIRTI JAIN,; KANIL KUMAR R.N,; SOMASHEKARAIAH.B.V, (International Journal of Pharma and Bio Sciences, 2015)
This study findings indicate that leaves Psychotria dailzelli, of possess significant pharmacological activities which comply with the claims made in the traditional medicinal texts. In the present work, the leaves of (family: Rubiaceae) have been investigated for screening phytochemicals. The qualitative and quantitative phytochemical analysis of Psychotria dailzelli. The fresh leaf extract were prepared using different solvents like Petroleum ether, Chloroform, Acetone, Ethyl acetate, Methanol to detect the active components. The presence of various phytochemical constituents in the extract is determined using standard screening tests and presence of alkaloids, terpenoids, tannins, saponins, are revealed. The phenolics and flavonoids content of Psychotria dailzelli species were determined in the present study. The phenolic content was determined using Folin-Ciocalteu assay. The total flavonoids were measured spectrophotometrically using the aluminum chloride colorimetric assay.